An investigation of the environmental niches of blown pack spoilage causing Clostridium estertheticum and Clostridium gasigenes on New Zealand beef and sheep farms. (September 2021) - Esteves, Eden; Gupta, Tanushree B; Whyte, Paul; Brightwell, Gale; Bolton, Declan
Abstract: The transfer of blown pack spoilage causing Clostridium spores from the farm to the meat plant is of growing concern to the meat industry. This study investigated the environmental niches of these Clostridium spp., specifically Clostridium estertheticum and Clostridium gasigenes in the beef and sheep farm environments in New Zealand. Faecal, soil, grass, drinking water, puddle water and feed (fodder beet, hay, bailage and silage, where available) samples were collected on five beef and sheep farms during Winter and Spring in 2018, in North and South Island, respectively. Beef and sheep farm samples were tested for C. estertheticum and C. gasigenes using enrichment plus PCR, qPCR and direct plating. C. estertheticum was detected in bovine faecal (4%), soil (2–18%) and grass (0–12%) samples at concentration of up to 2.0 log10  cfu/g. C. gasigenes were found in 18–46% of faecal, 16–82% of soil, 12–44% of grass, 0–44.4% of drinking water and 0–58.3% of puddle water samples tested and the direct counts ranged from 2.4 log10  cfu/ml in puddle water to 3.4 log10  cfu/g in soil. C. estertheticum were detected by qPCR in sheep farms in ovine feces (2.3%), soil (2.3%) and fodder beet (10%). All other sample types (grass, drinking water, puddle water, baleage, hay, silage and fodder beet) were negative using direct and enrichment plus PCR methods. In contrast C. gasigenes was detected in of faecal (22.7–38.6%), soil (22.7–84.1%), grass (17.5–34.1%) drinking water (35.7–78.6%), puddle water (33.3–40%), hay baleage (57%), silage (2%) and fodder beet (10%) at concentrations of up to 3.7 log10  cfu/g/ml. It was concluded that C. estertheticum and C. gasigenes were common on beef and sheep farms with the latter having higher incidence and mean concentration. Highlights: Higher prevalence of C. gasigenes than C. estertheticum on bovine and ovine farms. Culture-dependent and independent methods to test for blown pack spoilage spores. Blown pack spoilage Clostridium detected in grass and feed. Blown pack spoilage Clostridium detected in drinking and puddle water.